Applicability of Malaysian standards and universal design in public buildings in Putrajaya / Syazwani Abdul Kadir and Mariam Jamaludin - Abdul Kadir, Syazwani; Jamaludin, Mariam (Faculty of Architecture, Planning and Surveying, 2012)
This paper discusses an on-going research on universal design implementation in public buildilngs in Putrajaya with the applicability to Malaysian Standards of accessibility.